(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
In Ayurveda, Shalyatantra is one of the eminent branches based on six major methods of management among which Agnikarma is boon for local Vata and Kaphaja Vyadhi. Its effect can be assessed as Sthanik Karma (local action), Saarvadaihik Karma (Action throughout the body) and Vishista Karma (Special actions). Based on amount of Agni needed, the condition and site of disease, Dahanupakarana are used to produce therapeutic burns during Agnikarma Chikitsa. It can be classified according to Dravya used, site, disease, Akritiand Dhatu to be cauterized. Based on the Dagdha (Burn), it is again of four type viz. scorched burn, blistered burn, superficial burn and deep burn. Its indication is in all seasons except in summer and autumn. Indications and contraindications are well expounded in classics with detail information on Purva Karma, Pradhana Karma and Paschat Karma during Agnikarma as it is superior to every other procedure used in Ayurveda Surgery. In modern medicine, there is no use of therapeutical burn i.e., Samyak Dagdha Chikitsa but its use is in other form eg., Cauterization is used for coagulation and tissue destruction. Agnikarma is considered as the best therapy to pacify Kaphanubandha Vata Dosha because Agni possesses Ushna, Tikshna, Sukshma, Aashukari Gunas, which have anti Vataja and anti Kaphaja properties. It is done by red hot Shalaka. It gives quick relief to the patient and hence is termed as best therapy.